Diet of dominant frugivorous bat species in an oil palm landscape from Colombian Llanos: implications for forest conservation and recovery - Cely-Gómez, María Alejandra; Castillo-Figueroa, Dennis (THERYA, 2019)
Oil palm plantations have become a major agricultural landscape in the Neotropics, especially in Colombia, the largest oil palm producer in the region. The Orinoco, or Llanos, region of eastern Colombia is predicted to increase expansion for palm oil acreage over the coming decades, with implications for biodiversity loss. Describing dietary diversity of frugivorous bats is a functional approach to understanding the effect of oil palm dominated landscapes on bat-fruit interactions. Our objective was to characterize the diet of the dominant (most abundant) bat species present in an oil palm landscape from the Colombian Llanos. We compared diet breadth of bat species on the basis of Levin’s index and we assessed differences in the frequency of seed consumption through Chi-square tests (χ2). We calculated diet overlap with a Morisita-Horn index. We characterized diet breadth and overlap for four taxa (three species and one species complex) of bats from 149 fecal samples and 344 individual bats, from which we identified 13 seed species. Dietary composition differed significantly among bat species, as did diet breadth. Diet breadth was highest in Carollia spp. and lowest in Sturnira lilium. The greatest degree of diet overlap ocurred between Artibeus lituratus and A. planirostris and the lowest overlap between S. lilium and all the other species. Considering the functional identity of the plants dispersed by bats in our sample, where most of them are pioneer species that colonize disturbed areas, it is fundamental to preserve habitats such as forest fragments that maintain bat assemblages with diverse diets in agriculturally disturbed landscapes. This may have important implications in future restoration process at these sites.